Uncover the Underlying Mechanism of Drug-Induced Myopathy by Using Systems Biology Approaches - Dong Li; Aixin Li; Hairui Zhou; Xi Wang; Peng Li; Sheng Bi; Yang Teng (International Journal of Genomics)
Drug-induced myopathy (DIM) is a rare side effect; however, the consequence could be fatal. There are few reports to systematically assess the underlying mechanism of DIM. In this study, we curated the comprehensive DIM drug list based on structured labeling products (SPLs) and carried out the analysis based on chemical structure space, drug protein interaction, side effect space, and transcriptomic profiling space. Some key features are enriched from each of analysis. Specifically, the similarity of DIM drugs is more significant than random chance, which shows that the chemical structure could distinguish the DIM-positive drugs from negatives. The cytochrome P450 (CYP) was identified to be shared by DIM drugs, which indicated the important role of metabolism in DIM. Three pathways including pathways in cancer, MAPK signaling pathway, and GnRH signaling pathway enriched based on transcriptomic analysis may explain the underlying mechanism of DIM. Although the DIM is the current focus of the study, the proposed approaches could be applied to other toxicity assessments and facilitate the safety evaluation.